Quorum Sensing Methods and Protocols - Rumbaugh, Kendra P.; Rumbaugh, Kendra P. (Methods in Molecular Biology,, 2011)
Since its early days in the 1990s, the Quorum Sensing (QS) field has grown from a few dozen laboratories, investigating the pathways, proteins, and chemicals that facilitate signaling in bacteria, to hundreds of groups that have integrated evolutionary biology, computer science, mathematics, engineering, and metagenomics to create an ever-expanding and dynamic field. In Quorum Sensing: Methods and Protocols, expert researchers provide an in-depth set of diverse protocols that span this broad area of study. Broken into three detailed sections, the volume covers the detection, isolation, and characterization of the QS signals made by both Gram- and Gram+ bacteria, determination of the function of QS signals in vivo, and the development of QS disruption strategies. Written in the highly successful Methods in Molecular Biology™ series format, chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and expert tips on troubleshooting and avoiding known experimental pitfalls. Comprehensive and cutting-edge, Quorum Sensing: Methods and Protocols serves as an invaluable collection of easily accessible techniques for scientists seeking to further our knowledge about bacterial communication and its relation to humanity.